Sikh Punjabi transnational families in Lisbon and Punjab: How are gender roles maintained and negotiated within Punjabi migrants’ transnational families in Lisbon and Punjab? - Lopes, Jessica (2020)
In recent years, Sikh Punjabi migration to Portugal has started gaining attention. While it was estimated that the first migrants started to move to Portugal in the early 1990ies, the community has long time stayed unnoticed. Sikhs in Portugal are predominantly young and male and a large part of them has at some point been in an irregular administrative situation. Drawing on a multi-sited ethnographic research using participant observation in different cities of Punjab and the Great Lisbon between 2017 and 2019, this dissertation aims to look at how gender roles are maintained and negotiated within Punjabi migrants’ transnational families in Lisbon and Punjab. First, it investigates the crucial role of gender in scoping migration projects to Portugal. While migration restrictions have the power to encourage or dissuade transnational family practices such as family reunification and transnational marriages, this work looks at how kinship rules and social norms operate across borders. Secondly, this work looks at the gendered division of labor in Sikh Punjabi transnational families. It examine the work of women both in origin and abroad. This dissertation establishes that at the present moment, transnational family practices have not led to a more egalitarian division of roles within the Sikh Punjabi family living between Lisbon and Punjab and that while new challenges are faced by, both men and women, caring expectation perpetuate conventional gender norms of the family even in the transnational context.